Pengaruh Pemanfaatan Internet Terhadap Motivasi Belajar Siswa SMA di Wonogiri - Sri Tomo; Bambang Satrionugroho (Politeknosains, 2019)
Limited learning facilities and means, learning resources and human resources are problems that are often faced by high schools in the process of learning that utilizes information technology. The purpose of this study was to determine the effect of the benefits of the internet on student learning achievement, especially in terms of media internet access and internet access places in Wonogiri district. Data retrieval is done by questionnaire distribution method, then validity test, reliability test and normality test from the data that has been taken then hypothesis testing is done with linear regression. The results of the study show that the media access the internet and the place of internet access have a positive and joint effect on the improvement of student learning achievement.